2011
DOI: 10.4314/sajas.v40i4.65259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of licorice extract and a prebiotic on performance and blood metabolites of broilers

Abstract: Six hundred Ross 308 male broiler chickens were used to study the effect of licorice extract and the prebiotic, fermacto, on performance, blood metabolites and gastro-intestinal transit time (GTT) of feed in the birds. The birds were fed according to a three phase feeding programme on a starter, grower and finisher diet during the ages of 1 -14 day, 15 -35 days and 35 -49 days of age, respectively. The basic diets during each phase contained either 100 or 95% of recommended digestible amino acid (RDAA) concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
23
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 31 publications
10
23
2
Order By: Relevance
“…These results are in agreement with those of Pooryousef and Hosseini (2012), who indicated that carcass percentage and carcass component ratios were not affected by addition of licorice root extract and probiotic in Japanese quail diets. Sedghi et al (2010) added LE to broiler diets and did not find any effect on relative weight of carcass and body parts such as breast, femur, liver, heart, spleen and bursa, in line with the present results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in agreement with those of Pooryousef and Hosseini (2012), who indicated that carcass percentage and carcass component ratios were not affected by addition of licorice root extract and probiotic in Japanese quail diets. Sedghi et al (2010) added LE to broiler diets and did not find any effect on relative weight of carcass and body parts such as breast, femur, liver, heart, spleen and bursa, in line with the present results.…”
Section: Discussionsupporting
confidence: 90%
“…Although a limited number of reports on use of licorice extract in broiler nutrition have been published, the results have been inconsistent. Neither Sedghi, Golian, Kermanshahi, and Ahmadi () nor Salary, Kalantar, Sahebi, Ranjbar, and Hematimatin () found significant improvement of BWG of broilers when supplementing their diet (0.05%, 0.1% and 0.2%) or water (0.2% and 0.4%) respectively with licorice extract. Al‐Daraji () showed that licorice extract, especially at the level of 450 ppm, effectively diminished the detrimental effects of aflatoxicosis on the general physiological status of broiler chickens.…”
Section: Discussionmentioning
confidence: 93%
“…Lee et al (2004) discussed that essential oils could inhibit hepatic 3-hydroxy-3-methylglutaryl coenzyme A -which is involved in cholesterol synthesis-while Rahimi and Khaksefidi (2006) reported that probiotics are able to reduce cholesterol absorption and synthesis in the gastrointestinal tract of broilers. However, these hypotheses do not seem to be confirmed in our study, which is in agreement with results by Sedghi et al (2010), who supplemented broiler diet with 2 g/Kg Fermacto. Our results differ with those by Bölükbaşi et al (2006), who showed an increase of serum triglyceride and HDL in broilers fed 1 g/Kg thyme oil, and with those by Ebrahimi et al (2012), who showed that probiotics reduce serum cholesterol in broilers.…”
Section: Discussioncontrasting
confidence: 57%
“…Blood cholesterol concentrations decreased significantly in birds receiving the highest liquorice dose. A reduced abdominal fat content was found at all doses (Sedghi et al, 2010); because of this a NOAEL could not be derived. Kobuke et al (1985) found no effect on the incidence of any tumour when disodium glycyrrhizinate was administered to B6C3F 1 mice at concentrations of up to 0.15 % (males) or 0.3 % (females) in drinking water for 96 weeks in a carcinogenicity study.…”
Section: Repeated-dose Toxicity Studiesmentioning
confidence: 82%